CREATION OF FAMILY EMPLOYMENT PROGRAMME UNDER WATERSHED MANAGEMENT: A CASE STUDY KARKARA VILLAGE, DIST.-HAZARIBAGH - Mishra, K.; Basu, P.K. (Journal of Soil and Water Conservation, 2022)
• Rural Employment Generation Ptogramme is one of the aims under watershed development programme. A pilot project has been implemented at Karkara village, Dist. Hazaribagh through the Resource Management with the objective to create a continuous employment programme. A Biological Nursery with Horticulture species has been raised permanently by the watershed imptvvement society. Transfer of technology on vegetative propagation to the watershed people through participation of training programme conducted by D. VC. . Initially this project is funded partly by the Indo-German Bilateral Project through the Ddmodar Valley Corporation and partly by watershed beneficiaries. At present 10 families are getting employment opportunity regularly. The project has attained the break even point. This project found to be self-sufficient and to provide employment continuously to atleast 5 families in a year This continuous self-employment generating scheme has also helped the Eco Development Prograintne in the watershed through horticulture plantation in the land of farmers.